2019
DOI: 10.1016/j.physa.2018.10.035
|View full text |Cite
|
Sign up to set email alerts
|

The jamming transition is a k-core percolation transition

Abstract: We explain the structural origin of the jamming transition in jammed matter as the sudden appearance of k-cores at precise coordination numbers which are related not to the isostatic point, but to the emergence of the giant 3-and 4-cores as given by k-core percolation theory. At the transition, the k-core variables freeze and the k-core dominates the appearance of rigidity. Surprisingly, the 3-D simulation results can be explained with the result of mean-field k-core percolation in the Erdös-Rényi network. Tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Further, weights of interactions and nonlinear threshold rules have been introduced to describe more complex dynamics [22,45,91]. Recently, the k-core was also applied as a precursor of the jamming transition in granular materials [92].…”
Section: K-core Percolation and Threshold Modelsmentioning
confidence: 99%
“…Further, weights of interactions and nonlinear threshold rules have been introduced to describe more complex dynamics [22,45,91]. Recently, the k-core was also applied as a precursor of the jamming transition in granular materials [92].…”
Section: K-core Percolation and Threshold Modelsmentioning
confidence: 99%
“…The concept of k-core was introduced in social sciences [14] to define network cohesion and was then applied in many other contexts [15], including the robustness of random networks [16], the structure of the internet [17,18], viral spreading in social networks [19], the large-scale structure of brain networks [20], and the jamming transition [21]. For a network of interacting species, the k-core is the portion of the network that remains after iteratively removing from the network all species linked to fewer than k other species (see Figs.…”
mentioning
confidence: 99%
“…It was found that the average contact number, namely the coordination number, is a key parameter in particle systems 66 . The coordination number determines the particle contact network and plays an important role in clogging transition 67,68 . Thus, in our study, we employ the coordination number to distinguish particles at different states.…”
Section: Resultsmentioning
confidence: 99%